(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
This paper analysis the stability o f the mining blocks in Estonian oil shale mines, where the room-and-pillar mining system is used. The pillars are arranged in a singular grid. The processes in overburden rocks and pillars have caused the subsidence of the ground surface. Statistical analysis o f the pillars cross-sectional area evaluated the calculations. Normal distribution control allows determing the stability of a mining block. By normal distribution of the pillars cross-section area a potential collapse of a mining block can be expected. Theoretical and in situ investigations in Estonian oil shale mines showed that their results are close to the modeling ones. The surface subsidence parameters will be determined by conventional calculation schemes. Presented method suits well for mining block stability analysis and spontaneous failure prognosis.